2015
DOI: 10.4049/jimmunol.1401615
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling 1 Is a Positive Regulator of TGF-β–Induced Prostaglandin Production in Human Follicular Dendritic Cell–like Cells

Abstract: PGs are emerging as important immune modulators. Since our report on the expression of PG synthases in human follicular dendritic cells, we investigated the potential immunoregulatory function of PGs and their production mechanisms. In this study, we explored the intracellular signaling molecules mediating TGF-β–induced cyclooxygenase (COX)-2 augmentation in follicular dendritic cell–like cells. TGF-β triggered phosphorylation of Smad3 and ERK, which were essential for the increase in COX-2 protein. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…For example, LPS-induced COX-2 expression was inhibited by ERK and p38 inhibitors, which was verified by the actual induction of phosphorylation of these MAPKs by LPS [18]. TGF-β-stimulated COX-2 induction also required ERK and p38 [19]. In the present study, we extended our previous reports and explored the intracellular pathway of PGE 2 -induced COX-2 expression in FDC-like cells.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…For example, LPS-induced COX-2 expression was inhibited by ERK and p38 inhibitors, which was verified by the actual induction of phosphorylation of these MAPKs by LPS [18]. TGF-β-stimulated COX-2 induction also required ERK and p38 [19]. In the present study, we extended our previous reports and explored the intracellular pathway of PGE 2 -induced COX-2 expression in FDC-like cells.…”
Section: Introductionsupporting
confidence: 80%
“…In this study, we further investigated the underlying intracellular mechanism by examining the potential role of ERK and p38 MAPKs in this process. Our earlier results suggest that both ERK and p38 molecules are involved in the signaling pathway to COX-2 expression [19]. First, the effects of PGE 2 on the phosphorylation degrees of ERK and p38 proteins were analyzed by immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CsA treatment for up to 24 h increased Smad 3 phosphorylation in rat glomerular mesangial cells [ 54 ]. Induction of the Smad pathway by TGF-β1 increases Snail expression [ 55 ], a known regulator of EMT [ 56 , 57 ]. Studies by Cano and coworkers (2000) have shown that TGF-β1 can trigger EMT by decreasing expression of epithelial junction proteins through the activation of Snail [ 56 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…SOCS1 also plays a regulatory role in anaphylactic shock viscera injury processes [ 13 ]. SOCS1 promotes TGF-β-induced COX-2 expression and prostaglandin (PG) production by facilitating Smad3 phosphorylation and Snail binding to the COX-2 promoter [ 14 ]. The role of COX-2 in allergic inflammation and cellular interaction during allergic inflammation has been reported [ 15 ].…”
Section: Introductionmentioning
confidence: 99%